ANALISIS PERHITUNGAN PEMOTONGAN DAN PELAPORAN PAJAK PENGHASILAN ATAS PEMBELIAN BAHAN BAKU TERHADAP PEDAGANG PENGUMPUL PADA PT. DELTA PASIFIC INDOTUNA - Amin, Nabilah Nur Risfananda; Elim, Inggriani; Gerungai, Natalia Y.T. (Universitas Sam Ratulangi, 2019)
Clause 22 income tax which is deducted/collected by the collector is one of the sources of inland revenue (state income), which is deducted by certain agencies/companies appointed by the state to deduct PPh 22, and also the case with PT. The Pacific Delta Indotuna has been appointed by the government as the cutter/collector of clause PPh 22 from the collector as a supplier of raw materials for the fish canning industry. This study aims to analyze the role of business entity (PT Delta Pacific Indotuna) in calculating the tax deduction and reporting of clause PPh 22 that it is in accordance with the Income Tax Law and its implementation regulations. The research method that used is descriptive qualitative approach. The technique of data collecting uses direct surveys, interviews and documentation. Based on the results of the research conducted, it shows that the calculation of withholding of clause Income Tax 22 to the collector and its reporting is in accordance with Minister of Finance Regulation No.34/PMK.010/2017, concerning collection of income tax clause 22 with respect to payment for the delivery of goods and activities in the field of import or business activities in other fields.